Review of porous adsorbents for the separation of nitrogen from natural gas - Nandanwar, Sachin U.; Corbin, David R.; Shiflett, Mark B. (Industrial & Engineering Chemistry Research, 2020)
Natural gas is one of the critical fossil fuel sources in the world to fulfill current energy demand in the global market. Methane is the primary component in natural gas and its concentration is dependent on the source; a variety of impurities, such as nitrogen, carbon dioxide, oxygen, helium, hydrogen sulfide, water, and heavier hydrocarbons can be present, which reduces the overall fuel quality. Purification of natural gas is important in order to meet the U.S. pipeline and minimum heating value specifications. The separation of nitrogen from methane is challenging because of their similar molecular size (i.e., the two gases differ in kinetic diameter by only 0.16 angstrom). This Review discusses different methods for separating nitrogen from methane. Of these methods, pressure swing adsorption is one of the most effective techniques for separating nitrogen from natural gas using porous adsorbents, and encouraging results have been demonstrated in the past few decades. Many types of porous adsorbents are discussed here, including carbon molecular sieves, activated carbons, zeolites, titanosilicates, and metal-organic frameworks. Future trends and materials are discussed to put into perspective the new opportunities in this research area.